The Model Exponential GARCH (EGARCH) Untuk Memprediksi Harga Saham PT Merdeka Copper Gold Tbk - Agnes Eunike Sangian; Nelson Nainggolan; Deiby T Salaki (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2023)
The price of gold is determined by trading in the gold market and its derivatives. This study aims to determine the EGARCH model in predicting gold stock prices at PT Merdeka Copper Gold Tbk and to obtain the prediction results of the EGARCH model at PT Merdeka Copper Gold Tbk. There are two asymmetric GARCH response modeling techniques, namely the Threshold GARCH model (TGARCH) from Glosten, et al (1993) and Exponential GARCH (EGARCH) from Nelson (1991). The research results show that the ARIMA model (0,1,1) has the smallest AIC value of 6096.38. The GARCH model is obtained by GARCH (0,1), so it can be modeled using the EGARCH model. The EGARCH model obtained is EGARCH (1.7).